(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article examines the integration of sustainable tourism management within developing countries, focusing on the identification of prevalent challenges and the exploration of viable solutions. It delves into the intricacies of balancing economic growth with the imperative to preserve environmental integrity and promote social equity. Through a comprehensive analysis, the paper outlines strategic recommendations for enhancing sustainable tourism practices, emphasizing the role of multi-stakeholder collaboration, innovative financing, and community engagement. The findings highlight the potential of sustainable tourism as a catalyst for achieving broader sustainable development goals in developing nations.